Need Analysis of Android-Based Independent Learning Media Development for Elementary High School Students - Darma Surya, Adi (Jurnal Riset Ilmu Pendidikan, 2022)
This research is motivated by the Android-based independent learning media in elementary school learning that has not been effective so that it has not been able to significantly improve student learning outcomes. The purpose of this study was to determine the needs of elementary school high grade students for Android-based independent learning media. The research method used is a quantitative approach with the object of research being students and high school teachers in the surrounding Pariaman city. The instrument used is a questionnaire or questionnaire. The data analysis technique of this research is descriptive test. The results showed an average of >50% of students agreed to develop Android-based independent learning media, especially in Natural Science (IPA) subjects. This is supported by the availability of Android smartphone facilities with 95.2% of students already owning and using it with the intensity of use in the frequent category where the average student uses it for 1-3 hours / day and the age ranges from 6-12 months. Thus, it is necessary to develop Android-based learning media that is in accordance with the needs and characteristics of high school students